2011
DOI: 10.1074/jbc.m111.274068
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Validation of Acetyltransferase Activity of GlmU as an Antibacterial Target in Haemophilus influenzae

Abstract: Background: A search was initiated to identify inhibitors of the acetyltransferase domain of GlmU that could be exploited as starting points for new antimicrobials. Results: Sulfonamide inhibitors were identified that upon chemical modification displayed antimicrobial activity mediated via GlmU. Conclusion: Enzymatic inhibition of GlmU can lead to antimicrobial activity. Significance: For the first time, GlmU was validated as an antimicrobial target in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…The procedure was essentially that according to Hilliard et al (14), with modifications published previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was essentially that according to Hilliard et al (14), with modifications published previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al (8), by modeling acetyl-CoA into the apo structure of GlmU Mtb , suggested an interaction of Trp-460 and the substrate. Crystal structures of GlmU Hi (from Haemophilus influenzae) bound with acetyltransferase inhibitors were reported recently (21). These depict an important contribution by the equivalent Trp-449 in inhibitor binding.…”
Section: Ecmentioning
confidence: 99%
“…3,5 In addition, the acetyltransferase domain of GlmU has also been validated in vitro as an antibacterial target in Haemophilus influenzae, making it a suitable target for drug development. 6 The structure of GlmU enzyme and its mechanism has been revealed from the crystallographic studies of the GlmU enzyme with its substrates and inhibitors. The N-terminal domain (residues Asn3-Arg229) adopts an α/β fold similar to the dinucleotide binding Rossmann fold, whereas the C-terminal domain (residues Phe260-Ala437) catalyzes the acetyltransferase activity and adopts a left-handed parallel β-helix (LβH) structure homologous to bacterial acetyltransferases (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…10 Multiple screening strategies also led to the discovery of novel E. coli GlmU inhibitors, including arylamines 11 and aryl sulfonamides. 6,12,13 Recently, an in silico screening strategy using ligand-guided and structure-guided techniques led to the identification of two promising sulfonamide inhibitors. 14 Terreic acid is a reported antibacterial inhibitor, but its cellular and molecular targets are still unknown.…”
Section: Introductionmentioning
confidence: 99%